2003
DOI: 10.1210/en.2003-0320
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Endocrine Adaptation throughout Pregnancy to Nutritional Manipulation: Consequences for Maternal Plasma Leptin and Cortisol and the Programming of Fetal Adipose Tissue Development

Abstract: Maternal nutrient restriction at specific stages of gestation has differential effects on fetal development such that the offspring are programmed to be at increased risk of adult disease. We investigated the effect of gestational age and maternal nutrition on the maternal plasma concentration of leptin and cortisol together with effects on fetal adipose tissue deposition plus leptin, IGF-I, IGF-II ligand, and receptor mRNA abundance near to term. Singleton bearing ewes were either nutrient restricted (NR; con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(209 citation statements)
references
References 48 publications
11
192
2
4
Order By: Relevance
“…The observed decreases in circulating total IGF-I level and IGF-I:IGFBP-3 ratio for both mother and fetus in the presence of moderate maternal NR are consistent with other mammalian studies. In response to 60% global diet restriction in sheep pregnancy, Bispham et al [17] observed lower maternal total and free IGF-I levels and normal maternal glucose, consistent with our findings in the baboon. IGFBPs stabilize the IGF-I level across the 24-h period.…”
Section: Effects Of Maternal Nr On the Maternal And Fetal Igf-igfbp Asupporting
confidence: 91%
See 1 more Smart Citation
“…The observed decreases in circulating total IGF-I level and IGF-I:IGFBP-3 ratio for both mother and fetus in the presence of moderate maternal NR are consistent with other mammalian studies. In response to 60% global diet restriction in sheep pregnancy, Bispham et al [17] observed lower maternal total and free IGF-I levels and normal maternal glucose, consistent with our findings in the baboon. IGFBPs stabilize the IGF-I level across the 24-h period.…”
Section: Effects Of Maternal Nr On the Maternal And Fetal Igf-igfbp Asupporting
confidence: 91%
“…[7]). Global NR during pregnancy at levels similar to that in our study [17,18], and even more extreme restriction [19], has been extensively studied in sheep, pigs, and rats [17][18][19][20]. The IGF system within the placenta and several fetal organs has been shown to respond to both global and other forms of NR during pregnancy.…”
Section: Discussionsupporting
confidence: 66%
“…43,44 In sheep, maternal nutrient restriction over the period of rapid placental growth followed by restoration of maternal nutrition over the second half of gestation enhances the adipose tissue development at the end of gestation, which was thought to increase the risk of obesity in later life. 45 However, this does not lead to significant increase in adipose and fat mass at adulthood. 46 Bilateral uterine artery ligation performed on day 19 of gestation in rat leads to intrauterine growth retardation (IUGR).…”
Section: Animal Models For Programming Of Obesitymentioning
confidence: 99%
“…Du et al (2010) proposed that the fetal stage offers the greatest chance to improve the ability of livestock to deposit intramuscular fat due to a greater abundance of non-committed pluripotent cells. Studies utilizing sheep have reported adipose tissue in the fetus can be manipulated by maternal nutrition (Bispham et al, 2003;Ford et al, 2007). Research in sheep also indicates that maternal nutrition during gestation influences gene expression necessary for intramuscular adipocyte development (Tong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%